2019
DOI: 10.1371/journal.pmed.1002914
|View full text |Cite
|
Sign up to set email alerts
|

Early malaria infection, dysregulation of angiogenesis, metabolism and inflammation across pregnancy, and risk of preterm birth in Malawi: A cohort study

Abstract: BackgroundMalaria in pregnancy is associated with adverse birth outcomes. However, the underlying mechanisms remain poorly understood. Tight regulation of angiogenic, metabolic, and inflammatory pathways are essential for healthy pregnancies. We hypothesized that malaria disrupts these pathways leading to preterm birth (PTB).Methods and findingsWe conducted a secondary analysis of a randomized trial of malaria prevention in pregnancy conducted in Malawi from July 21, 2011, to March 18, 2013. We longitudinally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 76 publications
0
57
0
3
Order By: Relevance
“…Late initiation of ANC may lead to the late provision of IPTp-SP and insecticide-treated bed nets. As a result of the late initiation of IPTp-SP, pregnant women might be exposed to malaria in pregnancy, which may consequently lead to placental infection and adverse birth outcomes [29].…”
Section: Discussionmentioning
confidence: 99%
“…Late initiation of ANC may lead to the late provision of IPTp-SP and insecticide-treated bed nets. As a result of the late initiation of IPTp-SP, pregnant women might be exposed to malaria in pregnancy, which may consequently lead to placental infection and adverse birth outcomes [29].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from an area of low malaria transmission reported several factors that were associated with increased odds of SGA during P. falciparum -related MiP, including symptomatic malaria and infection after 12–16 weeks' gestation ( 24 ), In addition, the risk of SGA was reported to increase by 1.13 times for every episode of infection during pregnancy ( 24 ). In contrast, in areas of high malaria transmission and particularly when pregnant women received anti-malarials in the form of intermittent preventive treatment in pregnancy (IPTp), there was no association between number of malaria episodes and SGA, suggesting that the timing of MiP may contribute to increased risk of SGA ( 25 , 26 ). Indeed, placental pigment deposition (past-chronic infection) was associated with increased risk of SGA but not LBW or preterm birth, suggesting early chronic infection (usually outside of IPTp coverage) may drive SGA and not preterm labor ( 25 , 27 ).…”
Section: Causes Of Mip-associated Lbwmentioning
confidence: 99%
“…Malaria infection during early pregnancy leads to alterations in the vascular structure of the placenta, such as decrease of transport villi volume and increase of diffusion distance and diffusion vessel surface, which influence birth weight and gestational length [36]. Even so, Plasmodium infection mid-pregnancy has been linked increased risk of preterm birth, possibly due to the changes in angiogenic, metabolic, and inflammatory states [37].…”
Section: Introductionmentioning
confidence: 99%